Effectiveness of Group Guidance Services Using Shaping Techniques to Reduce Student Doomscrolling Behavior - Adella, Mutia; Siregar, Alfin (Yayasan Sembilan Pemuda Indonesia, 2025)
The purpose of this study is to determine the effectiveness of group guidance services using the shaping technique in reducing doomscrolling behavior among junior high school students. The method used is a quantitative approach with a quasi-experimental method employing a Nonequivalent Control Group Design (pretest-posttest). The research population consists of 50 students from the eighth grade of State Junior High School 1 Natal. The sample consists of 20 students selected through purposive sampling, consisting of 10 students in the experimental group and 10 students in the control group. The research instrument is a Doomscrolling Scale with 15 statement items using a Likert scale of 1–7. Prerequisite tests were conducted with normality tests (Shapiro-Wilk) and homogeneity tests, while data analysis used an independent sample t-test with the assistance of SPSS 25.0. The research results indicate a significant influence of the group guidance service using the shaping technique on the reduction of doomscrolling behavior, with a significance value of 0.000 (p < 0.05). The average doomscrolling score of the experimental group decreased from 77.50% to 30.70%, while the control group experienced an insignificant decrease, from 76.40% to 75.50%. The novelty of this study lies in the application of the shaping technique in the context of negative digital behavior, which has still been rarely studied in depth among high school students. The practical implications of these findings are that guidance teachers and school counselors can integrate the shaping technique into guidance programs to address excessive addiction to consuming negative content on social media. The contribution of this study adds empirical literature on behavior interventions based on psychological techniques in the fields of education and counseling, particularly related to digital mental health issues among adolescents.